IMPLEMENTASI BLACK BOX TESTING PADA WEBSITE EXTRAORDINARY - Gracezylia Todingrante; Sudirman; Afifah (KHARISMA Tech, 2022)
Abstract: This Extraordinary application is designed for people with ADHD or AttentionDeficit Hyperactivity Disorder, which is a disorder when a person has difficulty maintaining orcontrolling physical movements. This disease is mostly suffered by children, for that thetarget users of this application are parents of children with ADHD where this applicationprovides tutor services according to the needs of children with ADHD. This study aims toconduct a series of functional tests of the application both in terms of appearance and inputaction. This test uses the Black Box testing method of Equivalence Partitioning, andBoundary Value Analysis. The test results are good using valid data, random data, andincorrect data, all functional applications work as expected. Keywords: Implementation, Website, and Black Box.